Facilitating Communicative Ability of EFL Learners via High-Immersion Virtual Reality - Fang-Chuan Ou Yang; Fang-Ying Riva Lo; Jun Chen Hsieh; Wen-Chi Vivian Wu (Educational Technology & Society, 2020)
Developing communicative ability of English as a Foreign Language (EFL) learners is essential when it comes to authentic learning. Nevertheless, conventional textbook usage and English instruction often fail to be learner-engaging. With the help of high-immersion Virtual Reality (VR), language learning can be transformed into a more self-directed learning experience, using a simulated authentic environment to enhance engagement. Therefore, a three-dimensional learning system, Virtual Reality Life English (VRLE), was developed to provide learners with an authentic setting to facilitate communicative ability development. Seventy-two low-achieving junior high school students were recruited as participants. Multiple data sources were collected for both quantitative and qualitative data analysis of VRLE, including a pre-test/post-test addressing communicative performance, an Igroup Presence Questionnaire (IPQ) for the students’ perception of perceived presence, and a semi-structured interview. The primary affordances were the beneficial application of VRLE to English communicative ability and an enhanced sense of presence in an EFL context. Furthermore, the students were positive about the learning experience. The study proves the potential of incorporating high-immersion VR technology in an EFL context. Nevertheless, the challenge of its accessibility needs careful consideration in future research to place VR in an advantageous position for language learning.